The Affirmation – Tapping on Pain Perception and Serotonin Serum Level of Post – Caesarian Section patients - Joko Suwito; Suhartono Taat Putra; Agus Sulistyono (Universitas Airlangga, 2019)
Introduction: Affirmation - tapping interventions have been shown to reduce pain complaints in post-operative patients completing conventional treatment. This is thought to be due to serotonin performance but clinical studies have not been conducted. The aim was to compare the mean perception of the pain reported by post-operative patients given affirmation- tapping treatment with another treatment as a complementary nursing intervention. This was to see if the performance of the serotonin serum level is different from in other treatments.Methods: We used a randomized post-test only control group design carried out in parallel in post-caesarean section patients. The sample totaled 40 patients divided into four groups (10 in affirmation, 10 in tapping, 10 in affirmation-tapping and 10 in the control). They were obtained through simple random sampling. The instruments included affirmation-tapping guidelines, Elisa kits and the McGill - Melzack Pain Questionnaire short-form (MPQsf). The independent variable was the intervention of affirmation-tapping and the dependent variables were pain perception and serotonin level. The data was analyzed using simple linear regression.Results: The average variant of the serotonin levels in the affirmation-tapping treatment group was higher and thus differed significantly from the other groups.Conclusion: Affirmation-tapping as a complementary nursing intervention can increase the serotonin serum levels of the post-caesarean section patients by complementing conventional treatments. Participant pain complaints were lowest in the affirmation-tapping group with the highest serotonin levels present and these were significantly different to the other groups. Affirmation – tapping was recommended as a complementary intervention in nursing post-operative patients that complements conventional treatment.